Upper Limbs NCV study in Users of Hand Held Vibrating Tools (International Journal of Food and Nutritional Sciences, 2022)
Background: In the present world due to technological advancement many industrial instruments are being invented now and then to reduce the manual labour. The substantial changes have occurred in the in the pattern of working in the construction sector. The cutting instruments that are being used include chainsaws, hand drills, rock drills, and hand-held tampers.The use of various hand held vibrating tools is associated witheither HAVS, carpel tunnel syndrome (CTS) or both. Material & methods:In the present study 40 Construction workers using drill machines (concrete brokers & steel brokers) & 40 Controls (not exposed to hand vibration) were selected and Nerve conduction study (NCS) of both upper limbs was carried out. Motor & sensory nerve conduction of Ulnar, Median & Radial nerves was studied. Results of both the groups were compared.